Mpox in Nigeria: Perceptions and knowledge of the disease among critical stakeholders-Global public health consequences. - Olajoju J Awoyomi; Emmanuel O Njoga; Ishmael F Jaja; Felix A Oyeleye; Priscilla O Awoyomi; Musawa A Ibrahim; M A Saulawa; Haruna B Galadima; Adekunle B Rowaiye; Taiwo I Olasoju; Jamila A Idrisa; Folasade D H Olalere; et al. (PLoS ONE, 2023)
Background The mpox (monkeypox) disease is a re-emerging viral zoonosis of international concern that is endemic in parts of Africa. The mpox virus (MPXV), which was hitherto largely limited to some Central and West African countries, was declared a public health emergency of international concern by the WHO on July 23, 2022 following the rapid spread of the virus to non-endemic countries. Globally, as of March 16, 2023, the WHO had reported 86,496 laboratory-confirmed cases of mpox and 111 deaths in 110 countries. Of the 1,420 cases of mpox reported in Africa as of March 16, 2023, Nigeria alone recorded 57.1% (812) of the confirmed cases and eight fatalities recorded in the continent. To help improve on the understanding of the current situation in Nigeria, the present study assessed the perception and knowledge of mpox among Nigerian healthcare workers, academics and tertiary students. The study also sought to highlight the global public health significance of the MPXV, and recommend a One Health approach to limit exporting of the virus beyond the borders of Nigeria. Methods A web-based cross-sectional survey was conducted between 24 July 2022 and 12 August 2022 to evaluate the perception and knowledge of mpox among 1544 Nigerians, consisted of healthcare workers (n = 832), academics (n = 306) and tertiary students (n = 462). Data on the respondents' socio demographics and their information sources on mpox were also collected. Each correct response was allotted one point while an incorrect response was scored zero. The scores for perception and knowledge were dichotomized into positive (>5.5) and negative (≤5.5) and adequate (>5.8) and inadequate (≤5.8), respectively; using the average scores for perception and knowledge. The average score for perception and knowledge were summarised and presented as the mean and standard deviation (SD). Chi-square tests of association and binary logistic regression were carried out to determine factors associated with the outcome variables. Results Of the 1452 respondents that had heard of mpox, 878 (60.5%) and 419 (28.9%) had adequate knowledge and positive perception concerning MPXV infection respectively. Average perception score was 5.5. Mean perception and knowledge scores were 4.5(SD: 2.0) and 5.8 (SD: 1.9), respectively. Factors that were significantly associated with knowledge level were age (p = 0.020) educational qualification attained (p = 0.004), occupation (p<0.001), and geopolitical zone of residency (p = 0.001). There was a positive correlation between perception and knowledge scores (r = 0.4, p<0.001). Positive perceptions were likely among respondents who had tertiary education, and residing in North-west Nigeria. Likewise, adequate knowledge scores were likely among respondents under 30 years of age, with tertiary education or reside in North-west Nigeria. Sources of information were significantly associated with perception (p = 0.004) and knowledge (p<0.001) of the respondents. Conclusion The findings of this study show that there is disparity in the knowledge and perception of mpox in the study population, and as a result, there is a need to intensify awareness about MPXV infection to enhance positive perception among the respondents. This has potential to safeguard public health and contain the disease thus preventing it from spreading to the global community. A One Health approach involving animal and human health workers is imperative for improved knowledge and a good perception towards the disease among respondents, and enhanced active surveillance and early detection of MPXV in reservoir hosts (rodents and non-human primates); to prevent reverse zoonotic transmission of the virus at the human-animal interface.